2022
DOI: 10.1080/19490976.2021.2022407
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation by gut microbiota

Abstract: The gastrointestinal tract is continuously exposed to trillions of commensal microbes, collectively termed the microbiota, which are environmental stimuli that can direct health and disease within the host. In addition to well-established bacterial sensing pathways, microbial signals are also integrated through epigenetic modifications that calibrate the transcriptional program of host cells without altering the underlying genetic code. Microbiota-sensitive epigenetic changes include modifications to the DNA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 112 publications
4
120
0
Order By: Relevance
“…Recently, Ansari et al reported that commensal microbiota induced Tet2/3-dependent DNA methylation at regulatory elements of 'early sentinel' response genes, which is critical for maintaining intestinal homeostasis [70]. Our ndings extend this notion by revealing that Tet2-driven epigenetic regulation, tuned by gut microbiome, have an important role in remotely regulating pulmonary immune response [71].…”
Section: Discussionsupporting
confidence: 77%
“…Recently, Ansari et al reported that commensal microbiota induced Tet2/3-dependent DNA methylation at regulatory elements of 'early sentinel' response genes, which is critical for maintaining intestinal homeostasis [70]. Our ndings extend this notion by revealing that Tet2-driven epigenetic regulation, tuned by gut microbiome, have an important role in remotely regulating pulmonary immune response [71].…”
Section: Discussionsupporting
confidence: 77%
“…Epigenetic changes related to the gut microbiome include modifications to DNA or histones, as well as the regulation of non-coding RNAs [ 148 ]. For example, recent studies have shown that microorganisms can bind to lysine on histones and regulate host chromatin by modifying histone proteins [ 149 ]. In turn, post-translational modifications of histones induced by microorganisms lead to changes in transcriptional gene activity [ 150 , 151 ].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Microbiota is additional suppliers of methyl and acetyl needed by these epigenetic enzymes to perform their catalytic functions. Metabolic degradation of folate by microbiota produces the main substrate for DNA and histone methylation known as S-adenosylmethionine [ 106 ]. Therefore, the data provided here suggest that the relationship between microbiota and epigenetic regulation may prognosticate carcinogenesis in MM.…”
Section: Host Microbiome and Epigenetic Regulationmentioning
confidence: 99%